2014
DOI: 10.1002/rra.2856
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profiles Distinguish Channel Catfish from Three Reaches of the Lower Kaskaskia River and its Floodplain Lakes

Abstract: Running Title: Fatty acid biomarkers in riverine channel catfish KEY WORDS: fatty acids, catfish, Ictalurus punctatus, floodplain lakes, food webs 2 ABSTRACT Despite the increasing use of fatty acids (FAs) as biomarkers in aquatic food web analysis, little information is available regarding differences in FA profiles of fish among habitat types in riverfloodplain ecosystems. The objectives of this study were to 1) test whether the FA profiles of channel catfish (Ictalurus punctatus) differed among three reache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…DHA is selectively and highly retained over other PUFA in fish, consistent with all reviewed datasets. It is still not clear if the high retention of DHA in fish is mainly driven by dietary DHA (Dayhuff, ; Rude et al., ; Young et al., ) or by endogenous PUFA conversion (Henrotte et al., ; Hixson et al., ; Murray et al., ; Oboh, Betancor, Tocher, & Monroig, ; Tocher & Dick, ). Our results showed that DHA retention in fishes from subtropical rivers is greater than that from temperate rivers, suggesting fishes may spend extra energy to synthesise LC‐PUFA under high temperature leading to more energy loss (Farkas, Csengeri, Majoros, & Oláh, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…DHA is selectively and highly retained over other PUFA in fish, consistent with all reviewed datasets. It is still not clear if the high retention of DHA in fish is mainly driven by dietary DHA (Dayhuff, ; Rude et al., ; Young et al., ) or by endogenous PUFA conversion (Henrotte et al., ; Hixson et al., ; Murray et al., ; Oboh, Betancor, Tocher, & Monroig, ; Tocher & Dick, ). Our results showed that DHA retention in fishes from subtropical rivers is greater than that from temperate rivers, suggesting fishes may spend extra energy to synthesise LC‐PUFA under high temperature leading to more energy loss (Farkas, Csengeri, Majoros, & Oláh, ).…”
Section: Discussionmentioning
confidence: 99%
“…Algal PUFA variations induced by river longitudinal gradients significantly affected fish PUFA composition (Dayhuff, ; Rude et al., ; Young et al., ). Interacted with light availability, nutrient inputs and temperature, river longitudinal gradients also determine fish distribution (Buisson, Blanc, & Grenouillet, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations